Characteristics of Genome Editing Mutations in Cereal Crops. (January 2017) - Zhu, Changfu; Bortesi, Luisa; Baysal, Can; Twyman, Richard M.; Fischer, Rainer; Capell, Teresa; Schillberg, Stefan; Christou, Paul
Abstract : Designer nucleases allow the creation of new plant genotypes by introducing precisely-targeted double-strand breaks that are resolved by endogenous repair pathways. The major nuclease technologies are meganucleases, zinc-finger nucleases, transcription activator-like effector nucleases, and the CRISPR/Cas9 system. Each comprises a promiscuous endonuclease guided by protein–DNA or RNA–DNA interactions. A great deal is known about the principles of designer nucleases but much remains to be learned about their detailed behavioral characteristics in different plant species. The outcome of genome engineering reflects the intrinsic properties of each nuclease and target genome, causing variations in efficiency, accuracy, and mutation structure. In this article, we critically discuss the activities of designer nucleases in different cereals representing a broad range of genome characteristics. Trends: Genome editing strategies based on designer nucleases (meganucleases, ZFNs, TALENs, and CRISPR/Cas9) have revolutionized plant breeding by allowing the introduction of insertions, deletions and substitutions at pre-determined sites. The combination of genome editing and synthetic biology allows the creation of purpose-designed plants with precise sequence modifications. The current body of data suggests that the CRISPR, ZFN, and TALEN methods are more efficient than meganucleases. CRISPR (without enhancements) is more susceptible to off-target effects and great care is required during target selection to minimize the likelihood of unwanted mutations, particularly if the target has close paralogs in the genome. The most effective way to generate homozygous plants is to use the most efficient nucleases, express them at high levels and (for HDR) deliver large amounts of donor DNA. The outcome of both NHEJ and HDR editing seems to be consistent among the different methods, perhaps reflecting the overall similarity of the DSB repair mechanisms in cereals.